PD-1 Antibody Monotherapy for Malignant Melanoma: A Systematic Review and Meta-Analysis. - Zhijuan Lin; Xing Chen; Zhifeng Li; Yiming Luo; Zhihong Fang; Bing Xu; Mingzhe Han (PLoS ONE)
Antibodies targeting programmed death 1 (PD-1) help prevent tumor cells from escaping immune-mediated destruction. We conducted this systematic review and meta-analysis to gain insight into the efficacy of PD-1 antibodies for the treatment of melanoma. Five trials involving 2,828 adult patients were included in this meta-analysis. In patients with previously untreated or refractory melanoma, treatment with PD-1 antibodies significantly improved the six-month progression-free survival (PFS) (HR 0.55, 95% CI 0.50-0.60, P<0.00001) and the overall response rate (OR 3.89, 95% CI 3.12-4.83, P<0.00001). This meta-analysis indicated that anti-PD-1 treatment might provide a significant survival benefit in patients with melanoma. In addition, we found that patients treated with nivolumab reported significantly fewer treatment-related adverse events (OR 0.74, 95% CI 0.57-0.97, P = 0.03) than those treated with other agents, but there was a dose-dependent increase in the frequency of adverse events in patients treated with pembrolizumab.